A Reliability and Validity of an Instrument to Evaluate the School-Based Assessment System: A Pilot Study - Nor Hasnida Md Ghazali (International Journal of Evaluation and Research in Education (IJERE), 2016)
A valid, reliable and practical instrument is needed to evaluate the implementation of the school-based assessment (SBA) system. The aim of this study is to develop and assess the validity and reliability of an instrument to measure the perception of teachers towards the SBA implementation in schools. The instrument is developed based on a conceptual framework developed by Daniel Stufflebeam, that is the CIPP (context, input, process and product) Evaluation Model. The instrument in the form of questionnaire is distributed to a sample of 120 primary and secondary school teachers. The response rate is 80 percent. The content validity is assessed by the experts and the construct validity is measured by Exploratory Factor Analysis (EFA). The reliability of the instrument is measured using internal consistence reliability, which is measured by alpha coefficient reliability or Cronbach Alpha. The finding of this pilot study shows that the instrument is valid and reliable. Finally, out of 71 items, 68 items are retained.